Circulating zearalenone and its metabolites differ in women due to body mass index and food intake. (June 2018) - Mauro, T.; Hao, L.; Pop, L.C.; Buckley, B.; Schneider, S.H.; Bandera, E.V.; Shapses, S.A.
Abstract: The environmental estrogen, zearalenone (ZEA), is found in the food supply from Fusarium fungal contamination in grains and sometimes used as a growth promoter for beef cattle. Long-term exposure to ZEA and its metabolites may present health risk due to higher estrogenic activity. Serum ZEA metabolites were measured to determine the exposure and the association with food intake in 48 overweight/obese women (52 ± 9 years). The free and conjugated ZEA indicated the highest detection rate of all the metabolites. Conjugated ZEA and total ZEA metabolites were lower (p = 0.02) in overweight/obese than normal weight women, and free metabolites were either the same or showed a trend to be higher. In addition, those with highest (280–480 g/d) compared those with lowest (<115 g/d) meat consumption had higher conjugated serum ZEA metabolite concentrations (p < 0.05). Intakes of other food groups (i.e., dairy, cereal, etc.) were not associated with ZEA metabolites. These findings indicate that ZEA and its metabolites are detectable in nearly all women and concentrations are associated with greater meat intake, and influenced by body mass index. Determining how the food supply influences human concentrations of ZEA metabolites is warranted, as well as determining vulnerable populations. Highlights: The environmental estrogen, zearalenone (ZEA), is found in the food supply. There are limited studies examining ZEA and its metabolites, and in this study we found detectable serum levels in nearly all women. Serum conjugated ZEA metabolites was higher in women who consumed more meat products. Obesity lowered conjugated ZEA and total ZEA metabolites compared to normal weight, but not free concentrations.